PRIMARY CYTOMEGALOVIRUS INFECTION DURING PREGNANCY: Life Science-Microbiology - BERRY, DR. VANDANA; LAL, DR. MADAN (International Journal of Life Science and Pharma Research, 2012)
Cytomegalovirus (CMV) infection in pregnancy is too common occurring primarily as well as recurrently due to reactivation of latent infection. The primary CMV infection during pregnancy is associated with numerous complications like congenital malformations, intrauterine fetal death and later sequelae like blindness, deafness etc. In the present study, a total of 354 women coming for antenatal checkup were screened for CMV specific IgM antibodies. There was 22.03% positivity rate which is a matter of concern. This study promotes to introduce a mandatory screening of all females in child bearing age group for primary CMV infection along with proper education of all subjects regarding transmission and prevention of the infection